Malignant nodular hidradenoma-inguinal region clinically masquerading as squamous cell carcinoma: a case report - Vernekar, Sunita S.; Bargunam, Priyadharshini (International Journal of Research in Medical Sciences, 2019)
Malignant Nodular hidradenoma is an extremely rare aggressive tumour originating from eccrine sweat glands with an incidence of <.001%. So far less than 80 cases have been reported in the literature. It’s known for its local recurrence (50%) and metastasis (60%) and hence early diagnosis and radical treatment is mandatory. But differentiating it from its benign counterparts and other skin tumour mimics is challenging, due to its histopathological similarity & lack of diagnostic immunomarkers. Authors report a case of 65-year-old female who presented with a short 4-month history of rapidly growing ulceroproliferative growth in the right inguinal region with bilateral inguinal node enlargement, associated with pain and discharge. Wedge biopsy of left inguinal lymph node showed malignant cutaneous adnexal tumour deposits, which after excision was typed as malignant nodular hidradenoma. It was confirmed with immunohistochemistry. Patient presented with recurrence 8 months after excision.